2012
DOI: 10.5430/wje.v2n4p64
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Linguistic Knowledge, Metacognitive Knowledge and Metacognitive Strategy Use in Speaking and Listening Proficiency of Iranian EFL Learners

Abstract: This study examined the influence of language knowledge, metacognitive knowledge and metacognitive strategy use on speaking and listening proficiency. Ninety six freshman and sophomore Iranian university students (male=6, female=90) were participated in the study. Two kinds of questionnaire and one lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 81 publications
2
7
0
Order By: Relevance
“…While some researchers have declared no significant effect for listening metacognitive strategies training on improving listening comprehension (Thompson and Rubin, 1996;Seo, 2002;Chen and Huang, 2011;Abdul Malik et al, 2013), others have emphasized the positive impact of strategy training on listening comprehension. This finding of the study is in line with the findings of some other related studies (Goh, 2002a;Pintrich, 2002;Bolitho et al, 2003;Chamot, 2005b;Annevirta et al, 2007;Vandergrift, 2007;Field, 2008;Coşkun, 2010;Ghapanchi and Taheryan, 2012;Maftoon and Fakhri Alamdari, 2020;Panggabean and Triassanti, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…While some researchers have declared no significant effect for listening metacognitive strategies training on improving listening comprehension (Thompson and Rubin, 1996;Seo, 2002;Chen and Huang, 2011;Abdul Malik et al, 2013), others have emphasized the positive impact of strategy training on listening comprehension. This finding of the study is in line with the findings of some other related studies (Goh, 2002a;Pintrich, 2002;Bolitho et al, 2003;Chamot, 2005b;Annevirta et al, 2007;Vandergrift, 2007;Field, 2008;Coşkun, 2010;Ghapanchi and Taheryan, 2012;Maftoon and Fakhri Alamdari, 2020;Panggabean and Triassanti, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The most used metacognitive strategy is the specified statement "I pay attention when someone is speaking English.". This supports previous studies that indicated speaking has the highest correlation with the metacognitive language learning strategy, (Forbes & Fisher, 2018;Ghapanchi & Taheryan, 2012). Nelson and Narens (1994), who developed the monitoring and control theory asserts that metacognition can essentially be divided into 2 sections: 1) monitoring and 2) control.…”
Section: Discussionsupporting
confidence: 88%
“…. In enhancing the English learning process, they were estimating speaking knowledge process by doing planning and controlling the language strategy used (Ghapanchi & Taheryan, 2012). Utilizing online platforms such as movies, TV shows, or YouTube as social media has influenced students' learning speaking ability (Sze, 2006).…”
Section: Metacognitive Strategiesmentioning
confidence: 99%